2013
DOI: 10.1093/jxb/ert144
|View full text |Cite
|
Sign up to set email alerts
|

Graft union formation in grapevine induces transcriptional changes related to cell wall modification, wounding, hormone signalling, and secondary metabolism

Abstract: Grafting is particularly important to the cultivation of perennial crops such as grapevine (Vitis vinifera) because rootstocks can provide resistance to soil-borne pests and diseases as well as improve tolerance to some abiotic stresses. Successful grafting is a complex biochemical and structural process beginning with the adhesion of the two grafted partners, followed by callus formation and the establishment of a functional vascular system. At the molecular level, the sequence of events underlying graft unio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
134
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(140 citation statements)
references
References 34 publications
5
134
0
1
Order By: Relevance
“…The scion CS was grafted onto RG (CS/RG) and 1103P (CS/1103P) as well as autografted onto CS rootstocks (CS/CS) (as described by Cookson et al , 2013). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scion CS was grafted onto RG (CS/RG) and 1103P (CS/1103P) as well as autografted onto CS rootstocks (CS/CS) (as described by Cookson et al , 2013). …”
Section: Methodsmentioning
confidence: 99%
“…Many genes were differentially expressed over time, from 3 to 28 d after grafting, but they will not be discussed here as they have been described previously (Cookson et al , 2013). The scion/rootstock graft interfaces studied were: the autograft Vitis vinifera cv.…”
Section: Introductionmentioning
confidence: 99%
“…7 When transcriptome of grapevine rootstock and graft interface tissues sampled 3 and 28 dag were studied in homo-grafts (CS grafted with itself), we observed that homo-graft union development in grapevine involved the upregulation of many genes involved in cell wall synthesis, wound responses, secondary metabolism and signaling. 4 These gene expression differences were accompanied by the accumulation of callose, lignin and cellulose in the callus cells at the graft interface (Fig. 1.…”
Section: Transcriptional Changes During Graft Union Formation Overlapmentioning
confidence: 99%
“…Up until very recently, the only gene expression studies published on grafting concerned homo-grafting where processes presumably similar to simple wound-like responses 6,7,4 seem to occur.…”
Section: Hetero-grafting Triggers the Up-regulation Of Stress And/or mentioning
confidence: 99%
“…The mechanism of graft incompatibility of grapevine is not fully understood. Researchers studied how the union develops and functions over time (Pina, Errea 2005;Darikova et al 2011;Cookson et al 2013), and confirmed that incompatibility between different scion-rootstock combinations my occur (Gökbayrak et al 2007). This incompatibility can be detected few weeks after grafting and linked to a poor vascular connection and phloem degeneration at the graft union.…”
mentioning
confidence: 93%